2000
DOI: 10.1007/bf02726173
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent nutrition in a rural community in Bangladesh

Abstract: The objective of this study was to assess the nutritional status of adolescent boys and girls in a rural community in Bangladesh. Between December 1996 and January 1997, a cross-sectional survey was carried out in 803 households, each containing at least one adolescent, sampled consecutively from four purposely-selected villages in Rupganj Thana, Narayanganj district. Initially, the guardians of 1483 healthy and unmarried 10-17 year old adolescents (51% boys and 49% girls) were interviewed about family structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
48
6
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 5 publications
9
48
6
1
Order By: Relevance
“…2). A similar trend has been reported that the prevalence of thinness decreased with age 1,8,10,29,41 . 26 and West Bengal (32.00%) 10 .…”
Section: Discussionsupporting
confidence: 87%
“…2). A similar trend has been reported that the prevalence of thinness decreased with age 1,8,10,29,41 . 26 and West Bengal (32.00%) 10 .…”
Section: Discussionsupporting
confidence: 87%
“…In urban, median weight ranged from 28 kgs to 55 kgs from 10 to 19 years and those of rural students, it was from 24 kgs to 47 kgs. Median weight was less than NCHS values 6 of median age for each group from 10 to 19 years.…”
Section: Discussionmentioning
confidence: 67%
“…In contrast, the potential correlation between menarche and nutrition is a concern in this sample: the rate of acute malnutrition in rural Bangladesh was 10.7 percent in 1999 (World Health Organization Global Database on Child Growth and Malnutrition 1999; see also Shahabuddin et al 2000). The extent to which this poses a problem for our analysis depends on whether differences in nutrition are large enough to exert an influence on endocrine systems.…”
Section: A Endogenous Instrumentsmentioning
confidence: 87%